Annular Pancreas as A Cause of Neonatal Duodenal Obstruction: A Case Report - Karishma Siraj; Saqib Zaman; Lyaba Atta; Fatima Shafiq; Haseena Ali; Mohammad Waqar (Journal of Gandhara Medical and Dental Sciences, 2025)
The annular pancreas is a rare congenital anomaly that encircles a portion of the duodenum, causing duodenal obstruction with a wide range of clinical presentations. In neonates, it is one of the primary causes of duodenal obstruction, presenting as frequent vomiting, dehydration, abdominal distention, and tenderness. In adults, it can present as pancreatitis, duodenal or gastric outlet obstruction, or stenosis. This condition should be recognized early, as early intervention yields better outcomes. We present a case of a 6-day-old neonate with duodenal obstruction caused by the annular pancreas—the neonate presented with persistent vomiting and abdominal distention with severe dehydration and electrolyte derangements. X-ray of the abdomen showed a classic double bubble sign indicative of duodenal obstruction. The infant underwent resuscitation with intravenous fluids, analgesics, and a surgical laparotomy. Where the bowel was decompressed and duodenodenostomy was performed. Postoperatively, the patient's recovery was uneventful, and he was discharged home. Feeding was gradually introduced with no complications. The rarity of this condition, its presentation, and its successful management have prompted us to present the case.